Celebrity chefs, food media and the politics of eating - Hollows, Joanne (Bloomsbury Academic, 2022)
"From clean eating to food hacks for those getting fit, celebrity chefs have penetrated the public consciousness when we think about food on a mass scale: looking at celebrity chefs demonstrates how food is caught up in so many aspects of contemporary politics, from the #MeToo movement to Brexit. Situated on the cusp of food studies and media studies, Joanne Hollows uses an interdisciplinary approach to understand the impact of celebrity chefs in how we think about food, and how we feed ourselves and others. Hollows explores the role of celebrity chefs in both the restaurant industry and media industries, and shows how digital media have enabled the emergence of new types of food personality through blogs, YouTube and Instagram. Starting with an overview and history of celebrity chefs, Hollows outlines the key trajectories in scholarship on celebrity chefs to date and then moves on to explore the impact of celebrity chefs on discussions around gendered labour and foodwork, food activism and ethical consumption and culinary travelogues. Drawing on over 15 years of research, Hollows identifies those chefs who have had crossover appeal in the UK and USA, including Ella Woodward, Jamie Oliver, Gordon Ramsay, Nigella Lawson and Joe Wicks and uses case studies to identify the surprising impact of celebrity chefs on contemporary culinary culture"